Investigation of key contributors of CO2 emissions in extended STIRPAT model for newly industrialized countries: A dynamic common correlated estimator (DCCE) approach - Ahmad Ghazali; Ghulam Ali (Energy Reports, 2019)
The study examined the impact of different forces on carbon dioxide emissions for ten newly industrialized countries (NIC's) by applying the extended STIRPAT model for the period 1991-2013. Moreover, study utilizes the regression of group mean dynamic common correlated estimator (DCCE) to analyze the relationship between carbon dioxide emissions (CO2), population, affluence, technology and extended factors such as labor productivity, urban employment level, population carrying intensity of real economy, energy mix, trade openness and energy intensity. The results from DCCE approach are compared with fully modified ordinary least square and dynamic ordinary least square techniques for robustness. Results of the study suggest that population, GDP per capita and CO2 emission intensity along with energy intensity are main contributors for CO2 emissions for NIC's, while population carrying capacity of real economy have no significant impact on CO2 emission level. Furthermore, energy mix and trade openness have marginal contribution in CO2 emissions. The policymakers can use these results to develop appropriate policies for economic growth through industrial development by curtailing the level of CO2 emissions.
Keywords: 330; CO emissions; Dynamic common correlated estimator (DCCE) regression; Extended STIRPAT; NIC's